Bubble connectivity in experimentally-sheared crystal-bearing silicic melts - Daffos, Camille; Martel, Caroline; Arbaret, Laurent; Champallier, Rémi (Comptes Rendus. Géoscience)
The explosivity of an eruption is mainly controlled by the ability of gases to escape the magma column. Indeed, magmas able to evacuate gases mostly erupt effusively whereas magmas that retain pressurised gases are likely to trigger explosive events. In order to evaluate the explosive potential of magmas residing at shallow level, we investigated the influence of crystal content and shear on the development of bubble connectivity in bubble- and crystal-bearing silicic melts. The pre-deformed samples contain 0 to 50 vol% of plagioclase crystals (40–90 $μ $m size) in a hydrated haplogranitic melt with 20–30 vol% vesicularity mainly consisting of decompression-induced H2O bubbles (${\sim }$20–250 $μ $m in diameter). The samples were deformed in torsion at a temperature of 650 °C (crystal-free) or 750 °C (crystal-bearing), confining pressure of 50 MPa, constant moderate shear rate of $2 × 10^{-4}~s^{-1}$, and low strains ($γ < 2$). The sample microtextures and three-dimensional pore network show that bubbles are mostly isolated in crystal-poor (0–10 vol%) samples, whereas bubble connection reaches more than 70% in crystal-rich (30–50 vol%) samples, whether deformed or not. With increasing strain from $γ = 0$ to 2, bubbles re-organise in shear zones by forming channels. Therefore, moderately-porous (20–30 bulk vol%) crystal-rich magmas emplacing at shallow depths, such as in upper conduits or lava domes, may be highly permeable via a process of gas channelling effective at very low strains ($γ < 2$). This implies that violent explosions of lava domes producing devastating surges require additional mechanisms of gas pressurisation in moderately-porous crystal-rich magmas.